Analisis Vegetasi Hutan Mangrove Di Kawasan Muara Sungai Serukam Kabupaten Bengkayang - Elvi Rusmiyanto Pancaning Wardoyo, Hariphin, Riza Linda (Universitas Tanjungpura, 2016)
The mangrove forest is one of the natural resources of the coastal area that serves to control the increase of boundary between groundwater level and seawater level inland (intrusion), to be a buffer zone, and to protect the shoreline so as to avoid erosion or abrasion. The research aimed to find out the composition and types of mangrove forest vegetation in the area of Serukam River estuary, Bengkayang Regency This research was conducted from June to September 2015 . The location was determined using a purposive random samplingmethod. There were three sampling locations with threeÂ transects in the mangrove forest of Serukam River estuary. There were six mangrove species found in the research, i.e. Sonneratia alba, Avicennia marina, Rhizophora mucronata, Bruguiera parviflora, R. stylosa, B. cylindrica. The highest density of trees and saplings was R. mucronata with a density of 113.3 Ind/Ha and The highest density of saplings was 32.73ind/ha. The highest density of seedlings was Bruguiera cylindrical, i.e. 16.66 ind/ha.